Pendampingan Mengembangkan LKS Berbasis Saintifik untuk Guru SD Kecamatan Sukamakmur Kabupaten Bogor, Jawa Barat - Suprayekti, Suprayekti; Hs, Zuhdy; Kustandi, Cecep (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2019)
The main problem faced by elementary school teachers in Sukamakmur Sub-district, Bogor Regency, to be able to apply learning with a scientific approach is the low quality of LKS used by teachers, so that an effort is needed to design, develop, utilize, and evaluate scientific-based worksheets for SD Sukamakmur Elementary Teachers Bogor Regency, West Java in a community service program. Through community service activities, solutions will be offered for the problems formulated above. The approach offered for the realization of the Community Service program is an empowerment model with the following steps: 1) Preparation Phase; 2) Assessment Phase; 3) Planning or Alternative Program Planning Phase; 4) Formulation Phase of the Action Plan; 5) Implementation Phase (Implementation) Program or Activity; 6) Evaluation Phase; and 7) Termination Phase. This service activity was held in three sessions, Session I was held on July 24, 2018, Session II was held on July 25, 2018 and session II was held on August 25, 2018, which was held in the Hall of PGRI Building, Sukamakmur Sub-District, Bogor Regency. The development of scientific-based worksheets has succeeded in increasing the ability of elementary school teachers to make worksheets, seen by the increase in the value of the product before and after the LKS construction took place. Elementary teachers who obtain a score of 60 or more in the initial LKS floating product increase to 84% in the final product of the LKS mining activity is completed. The development of scientific-based LKS is felt to be very beneficial for participants in an effort to improve the quality of the process and learning outcomes.